Pretty in pink [videorecording (Blu-Ray)] - Hughes, John, 1950-2009; Ringwald, Molly; Stanton, Harry Dean, 1926-2017; Cryer, Jon, 1965-; Potts, Annie; Spader, James; McCarthy, Andrew, 1962- (Paramount, 2022)
The high school girl from the wrong side of town goes to the prom with the wealthy heartthrob, but their romance is threatened by peer pressure.